Spectrophotometric Determination of Cinnamaldehyde from Crude Drugs and Herbal Preparations - Rind, F.M.A.; Memon, A.H.; Almani, F.; Laghari, M.G.H.; Mughal, U.R.; Maheshwari, M.L.; Khuhawar, M.Y. (Asian Journal of Chemistry, 2010)
A new spectrophotometric method has been examined for the analysis of cinnamaldehyde from cinnamon bark, cinnamon oils and herbal preparations. The method is based on the reaction of cinnamaldehyde through its aldehyde group with α-aminonaphthalene. The derivative formed exhibit a maximum absorbance which was measured at 376 nm with molar absorbtivity of 5.8 × 103 L mol/cm. A linear relationship was obtained between the absorbance and the concentration of the derivative which obeyed the Beer's law within 05-25 μg/mL. Cinnamaldehyde was extracted from cinnamon in ethanol. At the optimized conditions, the method was applied for the determination of cinnamaldehyde and amounts found were from cinnamon bark, cinnamon oils and herbal preparations 0.40-0.57, 0.44-46.00 and 0.003-0.340 % with (RSD) 0.01-0.03 %, 0.02- 1.52 % and (RSD) 0.015-1.99 % (n=3), respectively.